2020
DOI: 10.2147/amep.s231946
|View full text |Cite
|
Sign up to set email alerts
|

<p>Medical Student Perceptions of Emergency Medical Technician Training During the First Year of Medical School</p>

Abstract: Purpose: Medical schools look for ways to provide clinical experiences and skill development in connection with knowledge. One method used is to provide emergency medical technician (EMT) training to medical students; however, limited data are available concerning EMT training in medical education. Therefore, the aim of this study was to review student feedback about the EMT curriculum through multiple iterations of the curriculum. Methods: Students completed a voluntary school administered survey upon complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 12 publications
(12 reference statements)
0
15
0
Order By: Relevance
“… 24 We previously reported that the EMT curriculum made students more confident in their clinical skills and allowed students to practice patient-based care while interacting with other members of the health care team. 16 In addition to the coursework, students continue to have clinical experiences through their monthly EMS shifts in the first two years. The EMT program also introduces students to the small group work environment early in their medical school experience which affords the opportunity to establish relationships with their classmates, serves to promote class solidarity, and provides some time to become familiar with new expectations and routines of medical school prior to entering their more rigorous science coursework.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 24 We previously reported that the EMT curriculum made students more confident in their clinical skills and allowed students to practice patient-based care while interacting with other members of the health care team. 16 In addition to the coursework, students continue to have clinical experiences through their monthly EMS shifts in the first two years. The EMT program also introduces students to the small group work environment early in their medical school experience which affords the opportunity to establish relationships with their classmates, serves to promote class solidarity, and provides some time to become familiar with new expectations and routines of medical school prior to entering their more rigorous science coursework.…”
Section: Discussionmentioning
confidence: 99%
“…This is a continuation of work we have previously reported after the end of the first year where students perceived that they had a better understanding of their patient population. 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations